Oikeion and justice in Plato’s Republic - Murgier, Charlotte (ΠΗΓΗ/FONS, 2017)
This paper aims at investigating the notion of οἰκεῖον (one’s own) in Plato’s Republic, by assessing what it specifically adds to the Platonic account of justice. Although the investigation is mostly devoted to analyzing the relevant passages of Book IV where the definition of justice as oikeiopragia is elaborated, it starts with the first occurrences of the term οἰκεῖον in the former books of the Republic, showing how the notion is introduced to counter Trasymachus’ challenge and then philosophically re-fined in order to make sense of the Platonic claim that justice does not harm but rather favors one’s own good.